Primary Vaginal Myeloid Sarcoma: A Rare Case Report and Review of the Literature - Gaurang Modi; Irappa Madabhavi; Harsha Panchal; Apurva Patel; Asha Anand; Sonia Parikh; Pritam Jain; Swaroop Revannasiddaiah; Malay Sarkar (Case Reports in Obstetrics and Gynecology)
Myeloid sarcoma (chloroma, granulocytic sarcoma, or extramedullary myeloid tumour) is an extramedullary mass forming neoplasm composed of myeloid precursor cells. It is usually associated with myeloproliferative disorders but very rarely may precede the onset of leukemia. Here, we are presenting a rare case of primary vaginal myeloid sarcoma in a geriatric female patient without initial presentation of acute myeloid leukemia (AML). A 68-year-old female patient with ECOG Performance Score of 1 presented with pervaginal bleeding for 20 days. On colposcopic examination, she was found to have mass in the anterior fornix of vagina. A punch biopsy specimen revealed chloromatous infiltration of the vagina. LCA (leukocyte common antigen), MPO (myeloperoxidase), and c-kit were strongly positive on IHC (immunohistochemistry). The patient’s routine blood investigations were normal including peripheral smear, lactose dehydrogenase, uric acid, 2D echocardiography, conventional cytogenetics, bone marrow aspiration, and biopsy. The patient was given 4 cycles of decitabine (Decitex, manufactured by Sun Pharmaceutical Industries Limited, India), 20 mg/m2 for 5 days at an interval of 28 days. There was a partial response to decitabine according to RECIST criteria. As decitabine therapy was well tolerated, we are continuing in the same way until disease progression without any complications. The patient is undergoing regular follow-up at our centre.